SIMULASI PENENTUAN SUDUT ARAH KIBLAT DENGAN METODE SEGITIGA BOLA MENGGUNAKAN BAHASA PEMROGRAMAN GUI MATLAB R2009 - Asih Melati; Dwi Rohayati; Tatik Juwariyah (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2013)
This reseach is about qibla location measurement using analytical mathematics of spherical trigonometry. The analytical mathematics of spherical trigonometry is simulated using mathematics software. In This research using MATLAB R2009 mathematics software. Since this software user easily to use by newbie user, the language of this software simulated in GUI MATLAB R2009 programmer language. This programmer language make interactif learning between the user and the program. The important input parameter of this software are coordinat location of area then the user can measument angle magnitude qibla location convenient with coordinat location.